Determining Quorum of Attendance and Decision Making In the General Meeting of Shareholders Based on Court Stipulation Due To the Neglectful Absence of the Majority Foreign Shareholder in a Joint Venture Company (A Foreign Capital Investment Analysis - Hertanto, Ari Wahyudi (Indonesia Law Review, 2012)
The General Meeting of Shareholders (GMS) is one of the company’s organs with the significant role of determining the business course and other issues related to corporate actions; as it is granted by law to the shareholders of the company. Any decision can be made in the GMS; such as determining the shareholders’ unanimous concurrence on the proposed meeting agenda or even if the results of the meeting are actually contrary to such agenda caused by dissenting among themselves. However, the GMS can also pose certain obstacles in situations where one or more shareholders (that appear to be a majority shareholder) fail to act in good faith or have an internal dispute with other shareholder(s) in the company. The shareholder concerned can use such majority position to cause a dead-lock in the GMS, as a result of which the rest of the shareholder(s) are unable to make any decisions concerning the proposed GMS agenda. The aim of this article is to look at the effectiveness of Article 86 of the Indonesian Company Law for the purpose of overcoming the above described situation. The said Article 86 was formulated without considering the possibility of shareholders intentionally undertaking such unlawful measures. Moreover, the article is aimed at observing the concordance between the Indonesian Company Law and the Indonesian Procedural Law